Character Values of The Independent Learning Curriculum on The Profile of Pancasila Students in The Burlian Novel - Saifudin, Ahmad; Widiarini, Widiarini; Nafisatuzzahro', Nafisatuzzahro'; Utari, Utari; Musilawati, Fida Ayu (BRILIANT: Jurnal Riset dan Konseptual, 2024)
In reality the profile of the Pancasila youth is still not maximally achieved. Based on data from the Indonesian Child Protection Commission, in 2020 the number of children victims of violence in schools (bullying) increased to 76 students from 46 students in the previous year. One of the legendary novels that holds a lot of values is the novel entitled Burlian by Tere Liye. This novel contains educational aspects that are relevant to everyday life. This study is to identify the character values in independent learning curriculum of profile of Pancasila students that can be implemented to build studentsâ€™ character in the novel â€œBurlianâ€. The research method is qualitative research with intertext approach. The role of the researcher is a compulsory because the researcher is the key instrument in this study. The "Pancasila Student Profile" consists of six elements: (1) Faith, Fear of God, and Noble Manners, (2) Global Diversity, (3) Mutual Assistance, (4) Independence, (5) Critical Reasoning, (6) Creativity. The six characteristics included the Pancasila Student Profile. The instrument was used to assess the character in the Burlian Novel.Â  The results revealed that the character values in the Burlian Novel matched Pancasila Student Profile.Â  Â